Pyrosequencing Assay to Rapidly Detect Clarithromycin Resistance Mutations in Canadian Helicobacter pylori Isolates. (2009) - Slinger, R; Yan, L; Chan, F; Forward, K; Cooper-Lesins, G; Best, L; Haldane, D; van Zanten, S Veldhuyzen
Abstract : BACKGROUND: Mutations at positions 2142 or 2143 in the two-copy 23S ribosomal RNA gene of Helicobacter pylori are highly predictive of in vitro clarithromycin resistance and failure of clarithromycin-containing treatment regimens. OBJECTIVE: To design an assay to rapidly detect these mutations using rapid polymerase chain reaction and pyrosequencing, a novel method of 'sequencing by synthesis', and to test this assay with a collection of Canadian H pylori isolates. METHODS: Forty-two H pylori isolates (24 clarithromycin-resistant, 18 clarithromycin-susceptible) were studied. A target region in the 23S gene was rapidly amplified and sequenced by pyrosequencing. RESULTS: Mutations at one of the two positions studied were present in 20 of the 24 (83%) clarithromycin-resistant isolates; 13 had double-copy A2143G mutations, four had double-copy A2142G mutations and three had single-copy A2143G mutations. There were no mutations in 17 of the 18 (94%) susceptible isolates. A single-copy A2142G mutation was detected in one susceptible isolate. CONCLUSIONS: The pyrosequencing assay developed was able to detect and differentiate mutations at positions 2142 and 2143 in either one or both copies of the H pylori 23S ribosdomal RNA gene. Further study is needed to determine whether this pyrosequencing assay can be used to determine H pylori susceptibility to clarithromycin from clinical specimens such as stools or gastric biopsies.